Retorika Visual dalam Human Interest Fotografi di Instagram - Iin Soraya (Jurnal Komunikasi, 2022)
The trend of the use of instragram for Instagram photographers as a medium to display the results of his work, the process of making messages by the photographer in a photo to the process of delivering messages to the audience creates a visual rhetoric. Visual rhetoric is used to describe or explain visual images. Visual rhetoric is usually found on human interest photos. The purpose of conducting this research is to find out visual rhetoric on human interest photography works on Instagram. This study uses a constructivist paradigm, with data analysis techniques based on rhetorical theory, data collection techniques namely observation, documentation, and literature study. The results of the study are: Through the description of visual rhetoric theory which focuses on the subject or content, that is the type of photographic Vernacular Photography that presents normal everyday situations with an amateur concept. The object in this photo is a human being with a variety of activities, one of them playing Meaning here is a symbolic of freedom and happiness. Textures and details in the image using the freezing technique which freezes the timing and move (action). The composition used by photographers is the leading lines, the lines that lead to the main object, the rope as a guiding line. The narrative element in this photo tells how with simplicity but can be happy. Besides human intervention which is where a picture of a person's life in all situations and moods that cause audience sympathy.